Personhood, human nature and the foundations of fundamental rights in Martin Luther’s theology - Raath, A (Nederduitse Gereformeerde Teologiese Tydskrif, 2007)
This essay investigates the implications for the idea of fundamental rights of Luther’s views that the laws of political and legal development are not autonomous and independent of those of morality and religion; that religion may not become the servant of civilisation, law or politics, and that reason, the instrument for ordering civil and legal affairs, is informed by deeper driving forces of Christian religious commitment. It is found that Luther related his theological views, in this context, to the conscience of freedom and its corollary of freedom of conscience.